Rheology, physicochemical properties, and microstructure of fish gelatin emulsion gel modified by γ-polyglutamic acid - Xie, Huan; Sha, Xiao-Mei; Yuan, Ping; Li, Jia-Le; Hu, Zi-Zi; Tu, Zong-Cai (Frontiers in Nutrition, 2024)
In this work, the effect of γ-polyglutamic acid (γ-PGA) on the rheology, physicochemical properties and microstructure of fish gelatin (FG) emulsion gel was investigated.Emulsion samples were characterized by rheological behavior and stability prior to gelation. The mechanical properties and water holding capacity (WHC) were evaluated after gelation. The microstructure of the emulsion gel was further examined using confocal laser scanning microscopy (CLSM). Results indicated a gradual increase in the apparent viscosity and gelation temperature of the emulsion with an elevated concentration of γ-PGA. Additionally, frequency scan results revealed that FG emulsion with added γ-PGA exhibited a stronger structure. The emulsion containing 0.1% γ-PGA showed higher stability than that of the control. WHC and gel strength of the emulsion gel increased when γ-PGA concentration increased. CLSM images showed that γ-PGA changed emulsion gel structure, and the droplets containing 0.1% γ-PGA were evenly distributed. Moreover, γ-PGA could regulate the droplet size of FG emulsion and size distribution. These findings suggested that the viscoelasticity and structure of FG emulsion gels could be regulated by adjusting γ-PGA concentration of formulations. Improved rheology and physicochemical properties were shown by the γ-PGA modified FG emulsion gel. The results showed that γ-PGA modified FG emulsion gel may have broad application prospects in food, medicine, cosmetics and other industries.